2020
DOI: 10.3390/su12177205
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms and Enzymes Used in the Biological Pretreatment of the Substrate to Enhance Biogas Production: A Review

Abstract: The pretreatment of lignocellulosic biomass (LC biomass) prior to the anaerobic digestion (AD) process is a mandatory step to improve feedstock biodegradability and biogas production. An important potential is provided by lignocellulosic materials since lignocellulose represents a major source for biogas production, thus contributing to the environmental sustainability. The main limitation of LC biomass for use is its resistant structure. Lately, biological pretreatment (BP) gained popularity because they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 143 publications
(159 reference statements)
1
45
0
1
Order By: Relevance
“…The microbial community in the rumen is capable of degrading crude fiber that cannot be digested by a host animal, maintaining high metabolic performance and the health of ruminants. Anaerobic fungi are one of the first microorganisms in the rumen to colonize the fibrous tissue of plants, efficiently degrading the components of plant cell walls [ 19 ]. Before anaerobic fungi were confirmed to exist, the scientific community generally believed that fungi were obligate aerobic microorganisms.…”
Section: Taxonomy Distribution Metabolism and Fiber Degrading Ementioning
confidence: 99%
“…The microbial community in the rumen is capable of degrading crude fiber that cannot be digested by a host animal, maintaining high metabolic performance and the health of ruminants. Anaerobic fungi are one of the first microorganisms in the rumen to colonize the fibrous tissue of plants, efficiently degrading the components of plant cell walls [ 19 ]. Before anaerobic fungi were confirmed to exist, the scientific community generally believed that fungi were obligate aerobic microorganisms.…”
Section: Taxonomy Distribution Metabolism and Fiber Degrading Ementioning
confidence: 99%
“…The upgrading to biomethane can generally improve air quality and reduce greenhouse gas emissions. However, methane losses in the off-gas may affect the sustainability of the whole process [53][54][55][56][57][58].…”
Section: Resultsmentioning
confidence: 99%
“…2 and Table 1 shows the high content of TS & BOD (mg/l) in the sample indicating the presence of a higher number of microorganisms and organic matter. The organic matter (bacteria) breaks down the organic compounds of the silage (feedstock) and produces CH4, also higher BOD results in higher production of biogas [13]. With the characterization and determination of parameters that influence the biogas production [14], it was concluded that Napier grass silage with a pH of 4.59, least Total Solids of 4020 mg/l and the maximum BOD of 342.93 mg/l was expected to give the optimum rate of CH4 production.…”
Section: Pre-field Workmentioning
confidence: 99%